The Study on Teaching Present Continuous Tense Using Games at the Tenth Grade of SMAK Giovanni Kupang - Sene, Chamelya Vivi Crystanty; Tefa, Antonia (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The purpose of this research article is to address the following inquiries: (1) Can tenth-grade students proficiently acquire the present continuous tense through game-based instruction? (2) What is their proficiency level? (3) Do games effectively teach the present continuous tense to tenth grade students at SMAK Giovanni? To address those inquiries, the researcher used a descriptive method because it is used to describe the students’ mastery in the present continuous tense. The participants of the study consisted of tenth grade students from SMAK Giovanni Kupang. Fifteen students, who were all selected as subjects for the researcher's study, comprised the level. The researcher employed lesson plans and tests to get the data. The researcher devised three instructional approaches to teach the present continuous tense through the utilization of games. During the experiment, the researcher administered two tests: a pre-test and a post-test. Only three students demonstrated successful performance in the pre-test results. The class had a low level of proficiency. By incorporating game-based instruction, the students' performance and overall understanding of the subject matter showed noticeable improvement.